2006
DOI: 10.1140/epjc/s2006-02615-6
|View full text |Cite
|
Sign up to set email alerts
|

Small-x phenomenology – Summary of the 3rd Lund small-x workshop in 2004

Abstract: Abstract. A third workshop on small-x physics, within the Small-x Collaboration, was held in Hamburg in May 2004 with the aim of overviewing recent theoretical progress in this area and summarizing the experimental status.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 279 publications
0
43
0
Order By: Relevance
“…[37]), to achieve a full treatment of gluon coherence effects [38] capable of describing jet final states across the whole rapidity phase space. A uniform treatment of the high-energy and Sudakov regions is still an open issue [39] of interest for parton-shower implementations.…”
Section: Jhep09(2009)121mentioning
confidence: 99%
See 1 more Smart Citation
“…[37]), to achieve a full treatment of gluon coherence effects [38] capable of describing jet final states across the whole rapidity phase space. A uniform treatment of the high-energy and Sudakov regions is still an open issue [39] of interest for parton-shower implementations.…”
Section: Jhep09(2009)121mentioning
confidence: 99%
“…Observe that calculations based on the unintegrated formalism will in general depend on two scales, µ and the rapidity, or angle, cut-off [26,39,41]. See e.g.…”
Section: Jhep09(2009)121mentioning
confidence: 99%
“…x 1,2 are the longitudinal momentum fractions of the partons that are adjacent to the jets. Various works [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26] addressing the azimuthal 2 angle (θ) profile of the two tagged jets, suggest the presence of important minijet activity populating the rapidity interval which can be taken into account by considering a BFKL gluon Green function connecting the two jets. However, it was shown that the azimuthal angle behaviour of the tagged jets is strongly contaminated by collinear effects [27,28], that have their origin at the n = 0 Fourier component in θ of the BFKL kernel.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of this formalism can be found, for example, in the reviews in Refs. [21][22][23]. …”
mentioning
confidence: 99%
“…A detailed description of this formalism can be found, for example, in the reviews in Refs. [21][22][23]. We only mention that the main part of the higher-order QCD corrections (namely, NLO + NNLO + N 3 LO + · · · contributions, which correspond to the log 1/x enhanced terms in perturbative series) is effectively taken into account in the k T -factorization approach already at leading order, and it provides a solid theoretical ground for the effects of the initial parton radiation and transverse momenta of the initial quarks and gluons.…”
mentioning
confidence: 99%